If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(a + 2) + -2(2a + 5) = 18 Reorder the terms: 6(2 + a) + -2(2a + 5) = 18 (2 * 6 + a * 6) + -2(2a + 5) = 18 (12 + 6a) + -2(2a + 5) = 18 Reorder the terms: 12 + 6a + -2(5 + 2a) = 18 12 + 6a + (5 * -2 + 2a * -2) = 18 12 + 6a + (-10 + -4a) = 18 Reorder the terms: 12 + -10 + 6a + -4a = 18 Combine like terms: 12 + -10 = 2 2 + 6a + -4a = 18 Combine like terms: 6a + -4a = 2a 2 + 2a = 18 Solving 2 + 2a = 18 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2a = 18 + -2 Combine like terms: 2 + -2 = 0 0 + 2a = 18 + -2 2a = 18 + -2 Combine like terms: 18 + -2 = 16 2a = 16 Divide each side by '2'. a = 8 Simplifying a = 8
| 12x^2+24x-288=0 | | (7x+16)+(9x-12)=180 | | 15x+3x=180 | | 9t+-21=3(t+-7)+6t | | 4(3x+1)+4=13x+4 | | 15x-9-4x+9= | | n^2+n=45 | | 9l-22=23+4l | | X=-8+15 | | 4m+6=17 | | 13w+39= | | y-2=.666x-27 | | 3.3x-4.2=-0.4 | | y-(-5)=-11 | | 11y-7.5-7y=2 | | C=3.50p+550 | | 48+12s= | | 8(e+6)=3(e+33) | | -34+x+36=32 | | (2x+5)=(3x-8) | | 4(2b+-6)+11=8b+-13 | | 1.5y-7=0.5y | | 5+x+x=2x+6 | | y-7=-.5x-(-6) | | 4a+10=8a+2 | | 11x-(6x-5)=110 | | 3x-4y+5z=-1 | | (2x+10)=(7y-8) | | 2x+-8y=-4 | | 4a-10=8a+2 | | -(-2)+10(-6)= | | 10-6x=4+46 |